2018
DOI: 10.1088/1361-6560/aad9db
|View full text |Cite
|
Sign up to set email alerts
|

Exploration and application of phenomenological RBE models for proton therapy

Abstract: The relative biological effectiveness (RBE) of protons varies with multiple physical and biological factors. Phenomenological RBE models have been developed to include such factors in the estimation of a variable RBE, in contrast to the clinically applied constant RBE of 1.1. In this study, eleven published phenomenological RBE models and two plan-based models were explored and applied to simulated patient cases. All models were analysed with respect to the distribution and range of linear energy transfer (LET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
118
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 104 publications
(144 citation statements)
references
References 123 publications
9
118
1
Order By: Relevance
“…In addition, the difference of ΔDtruemax between the optimization techniques was larger when the OAR was closer to the CTV. Among the RBE models, Wilkens et al showed largest ΔDtruemax, followed by Wedenberg et al and McNamara et al This is the same trend observed in RBE for low α/βx in the high LET region reported in the literature . Figure 6(a) and 6(b) shows the comparison of the ΔD99 for the CTV in the case of )(αfalse/βx=3 and )(αfalse/βx=12, respectively.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In addition, the difference of ΔDtruemax between the optimization techniques was larger when the OAR was closer to the CTV. Among the RBE models, Wilkens et al showed largest ΔDtruemax, followed by Wedenberg et al and McNamara et al This is the same trend observed in RBE for low α/βx in the high LET region reported in the literature . Figure 6(a) and 6(b) shows the comparison of the ΔD99 for the CTV in the case of )(αfalse/βx=3 and )(αfalse/βx=12, respectively.…”
Section: Discussionsupporting
confidence: 69%
“…In the case of )(αfalse/βx=3, the ΔD99 calculated with the Wedenberg RBE model was smaller than McNamara RBE model. This probably resulted from the fact that in the case of low α/βx, the Wedenberg model gives a smaller RBE than the McNamara model in uniform dose regions where LET is small …”
Section: Discussionmentioning
confidence: 99%
“…We used the LQ‐based RBE model developed by McNamara et al Due to the large variation in the RBE estimates because of the fundamental differences in experimental databases, model assumptions, and regression techniques, we estimated the model dependence of our results using two other models . Different RBE models give different RBE ; however, in both models, the magnitude of RBE increase is not significant (lower than 0.03 and 0.06 at the water surface and 0.003 and 0.005 at the target center, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The uncertainties in the (α/β) x values should therefore be carefully assessed both when evaluating the RBE values presented here and when estimating normal tissue complication probability for specific endpoints. The RBE changes monotonously with (α/β) x for the ROR and MCN models 14 . The RBE for all (α/β) x values within the confidence intervals will therefore fall within the shaded regions in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…However, for the purpose of evaluating RBE in a clinical setting, this approach could lead to artificially high RBE values in cases where the dose is inhomogeneous and low in parts of the organ. The low dose regions would then contribute to a significant increase in mean or median RBE as the RBE, for most models, is inversely proportional with dose 14 , and in addition, low dose regions often have high LET d due to low energy scattered or secondary ions or neutrons. Considering the dose and LET d distributions for the heart (Fig.…”
Section: Resultsmentioning
confidence: 99%